PEOPLE ARE PART OF GOD AND GODS ARE PART OF NATURE - JANSON, KUNO (IJRDO - Journal of Social Science and Humanities Research, 2019)
Modern mainstream science denies the existence of a god or a collective subconsciousness. But studies on human and animal behaviour demonstrate that animals living in packs form a so-called superorganism who possesses its own consciousness. The consciousness of the human superorganism is studied through religion. In addition, it is also studied what physical data carrier transmits information from a person to transpersonal consciousness, also called collective subconsciousness. It is also studied what are the sources of information of the collective subconsciousness, and its rules of processing information. Studies have found that the collective subconsciousness has a huge effect on society, and that to ignore the collective subconsciousness could be harmful.